Cyclic Damage Accumulation in the Femoral Constructs Made With Cephalomedullary Nails - Hamandi, Farah; Whitney, Alyssa; Stouffer, Mark H.; Prayson, Michael J.; Rittweger, Jörn; Goswami, Tarun (Frontiers in Bioengineering and Biotechnology, 2021)
Background: The purpose of this study was to evaluate the risk of peri-prosthetic fracture of constructs made with cephalomedullary (CM) long and short nails. The nails were made with titanium alloy (Ti-6Al-4V) and stainless steel (SS 316L). Methods: Biomechanical evaluation of CM nail constructs was carried out with regard to post-primary healing to determine the risk of peri-implant/peri-prosthetic fractures. Therefore, this research comprised of, non-fractured, twenty-eight pairs of cadaveric femora that were randomized and implanted with four types of fixation CM nails resulting in four groups. These constructs were cyclically tested in bi-axial mode for up to 30,000 cycles. All the samples were then loaded to failure to measure failure loads. Three frameworks were carried out through this investigation, Michaelis–Menten, phenomenological, and probabilistic Monte Carlo simulation to model and predict damage accumulation. Findings: Damage accumulation resulting from bi-axial cyclic loading in terms of construct stiffness was represented by Michaelis–Menten equation, and the statistical analysis demonstrated that one model can explain the damage accumulation during cyclic load for all four groups of constructs (P > 0.05). A two-stage stiffness drop was observed. The short stainless steel had a significantly higher average damage (0.94) than the short titanium nails (0.90, P < 0.05). Long titanium nail group did not differ substantially from the short stainless steel nails (P > 0.05). Results showed gender had a significant effect on load to failure in both torsional and bending tests (P < 0.05 and P < 0.001, respectively). Interpretation: Kaplan–Meier survival analysis supports the use of short titanium CM nail. We recommend that clinical decisions should take age and gender into consideration in the selection of implants.